Research on Game-based Teaching of History Subject to Promote the Adolescent Metacognitive Ability - Feng, Jiarong; Yang, Chenxu; Yue, Rongbing (Transactions on Social Science, Education and Humanities Research, 2024)
Nowadays, the rise of streaming services has changed the way teenagers access entertainment content. At the same time, the aesthetic taste of young people has changed greatly, which requires classroom learning to integrate new elements to adapt to the psychological needs of current young students, so as to improve the overall effect of the classroom. it’s crucial to innovate educational approaches, and game-based teaching has a large potential. This study is designed to explore the application of game-based teaching in the field of history, and to deeply research using the case of Chinese historical figure Zhang Jian. Through questionnaire and research analysis of adolescent students, it explores the impact of game-based teaching on their learning history. According to the study, through game-based teaching, students’ interest in Zhang Jian and related historical events has significantly increased, and they know more about the historical knowledge. Moreover, game-based teaching also promotes the cultivation of students’ teamwork and problem-solving abilities. Overall, this study concludes that: Game-based teaching significantly advances the learning of history among young people, providing feasible innovative approaches for educational practice.